ANALISA BIAYA KEGAGALAN TERHADAP KUALITAS MEBEL (FURNITURE) DENGAN METODE COST OF POOR QUALITY DI CV. FAST AKSARA MULTIMEDIA - Jumadi Suratman; Yetti Meuthia Hasibuan; Rini Halila Nasution; Sumardi Juniawan Sinaga; Suriandi Suriandi (Jurnal Simetri Rekayasa, 2020)
CV.Fast Aksara Multimedia is a trading business in the field of furniture furniture that produces elementary student desks, elementary student chairs, teacher desks, teacher chairs, filing cabinets and blackboards. In the production process, there are still various problems including a lot of cutting materials that are not precise in their measurements and receiving raw materials that are not in accordance with company standards. This results in inappropriate products such as elementary school student desks and elementary student chairs. The purpose of this study is to determine the number of products that are not suitable and the costs incurred as a result of these products and can make improvements and reduce products that are not in accordance with the wishes of the company. In this case, the researcher uses the concept of Cost Of Poor Quality in determining internal failure costs and external failure costs in the furniture business. The results of product research that are not in accordance with the company's wishes are 1,068 units with costs incurred of Rp. 293,350,000. As for recommendations for improvements that can be made to reduce the cost of products that are not suitable, reduce precision in the production section and set standards for receiving raw materials and quality control for suppliers.